Effect of osmotic dehydration pretreatment of carrots - TIAN Hong-ping; WANG Jian-ping (浙江大学学报. 农业与生命科学版, 2003)
The influences of different factors in the osmotic dehydration efficiency of carrots were studied by the orthogonal experiment, which were the density of sucrose solution/%, ratio of solid to liquid/kg·kg-1, osmotic dehydration time/min, blanching, slicing direction, thickness of slice, and coring. The results showed that blanching was the most important factor influencing the dewatering rate; the high-density sucrose solution can be helpful to preserve the color; most of the dewatering happened in the first 120 minutes of dehydration; and the thinner was the slices, the higher was the dewatering rate. At last, the optimum method of osmotic dehydration of carrots was put forward.